2021
DOI: 10.1097/pg9.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in COVID-19-associated Multisystem Inflammatory Syndrome of Children—A Single Center Experience

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Acharya et al suggested that pancreatitis should be included in the MIS-C diagnostic criteria, due to its frequency and poor clinical course. [10] In our study, similar to the literature, we found that the rate of hospitalization in the intensive care unit is higher in the presence of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Acharya et al suggested that pancreatitis should be included in the MIS-C diagnostic criteria, due to its frequency and poor clinical course. [10] In our study, similar to the literature, we found that the rate of hospitalization in the intensive care unit is higher in the presence of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 90%
“…Gastrointestinal symptoms, which were thought to be less common in the early stages of the COVID-19 pandemic, have been reported more frequently after the identification of MIS-C. [3] It is increasingly recognized that gastrointestinal symptoms and signs are the most common clinical presentation of MIS-C. [8] Cases ranging from mild gastrointestinal symptoms such as isolated nausea and vomiting to severe manifestations such as terminal ileitis, pancreatitis, and acute abdomen have been reported. [9][10][11] Our study focused on MIS-C cases with gastrointestinal system involvement and evaluated the severity of gastrointestinal involvement, clinical features, laboratory findings, and clinical outcome. In a meta-analysis in which 8 studies including a total of 440 MIS-C cases were evaluated, it was reported that the age of the cases ranged from 7 to 10 years, with a dominance of male gender 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Following the disease definition, fever, rash, cardiac, and GIS involvement signs were reported to be the most common clinical findings of MIS-C, in several cohort studies [14,15 & ,47, [55][56][57][58]. We tried to summarize the main characteristics of MIS-C patients in Table 1 There are also other miscellaneous cases whose cardinal signs have been uncommon such as acute pancreatitis, encephalopathy, cerebellitis, diabetic ketoacidosis, hepatitis, acute appendicitis, mesenteric lymphadenopathy, ocular myasthenia, and papilledema [70][71][72][73][74][75][76][77][78]. Despite the common similarities between Kawasaki disease and MIS-C, only one MIS-C case has been reported to have erythema and induration of Bacillus Calmette-Guerin (BCG) scar so far [79].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…There are also other miscellaneous cases whose cardinal signs have been uncommon such as acute pancreatitis, encephalopathy, cerebellitis, diabetic ketoacidosis, hepatitis, acute appendicitis, mesenteric lymphadenopathy, ocular myasthenia, and papilledema [70–78]. Despite the common similarities between Kawasaki disease and MIS-C, only one MIS-C case has been reported to have erythema and induration of Bacillus Calmette–Guerin (BCG) scar so far [79].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Pancreatic damage is, however, caused by changes in lipase levels. Acharyya, Bhaswati C DCH, MD(Ped), DNB(Paed), DNB(Gastro), MRCPCH(UK), FRCPCH(UK) * ; 4 A retrospective study analyzing data from 17 patients diagnosed with MISC-C and pancreatic impairment.…”
Section: Case Description Commentsmentioning
confidence: 99%